Refurbishment: a study of critical factor to be considered for building refurbishment / Nor Ain Mohd Nor - Mohd Nor, Nor Ain (Faculty of Architecture, Planning and Surveying, 2009)
This paper focuses on the refurbishment factor to be considered before carried out building refurbishment and issues related to refurbishment. As today, most people wish to preserve their heritage building and have attached them to the idea of refurbishment, more for economic reasons than reasons for historical and heritage. Building refurbishment scope is much wider and nowadays has been apply to variety of building include residence, office, hotel, restaurant, gallery and others. But before refurbishment conducted, the clients will firstly consider factors influence their decision. Based on the research that has been conducted to client and consultant, cost of finance to the whole project (economy) is the critical factor to be considered for building refurbishment as compared to others factors. This factor is important because the work is done to gain profit from the expenditure and act as future investment to building.